Mesenteric Inflammatory Venoocclusive Disease in a Patient with Sjögren’s Syndrome - Raquel Rios-Fernández; José-Luis Callejas-Rubio; Mercedes Caba-Molina; Rosa Ríos-Peregrina; Norberto Ortego-Centeno (Case Reports in Medicine)
Mesenteric inflammatory venoocclusive disease is an uncommon cause of intestinal ischemia. Certain diseases, such as hypercoagulation disorders, autoimmune diseases, or drugs have been associated with the pathogenesis of mesenteric inflammatory venoocclusive disease. Here, we report a patient with Sjögren’s syndrome who underwent surgery for suspected acute appendicitis with a subsequent pathological diagnosis of mesenteric inflammatory venoocclusive disease.